Entrepreneurship Education: Fostering the Entrepreneurial Spirit of Higher Education Tarbiyah Faculty Students in Aceh - Silahuddin, Silahuddin; Saiful, Saiful; Rijal, Fakhrul; Lismijar, Lismijar; Zarrazir, Alifia (AL-ISHLAH: Jurnal Pendidikan, 2024)
Entrepreneurship education is oriented towards offering concepts to develop interest, train, and form business actors. Therefore, the purpose of this study is to identify the concept of entrepreneurship education developed in the Tarbiyah faculty of higher education in Aceh, to describe the process of implementing entrepreneurship education in fostering the entrepreneurial spirit of higher education Tarbiyah faculty students at Aceh. This research uses a qualitative method where the researcher thoroughly examines the facts at the research location according to the focus of the problem, by researching directly at the research location, then the data from the analysis is presented and a discussion of data collection techniques through observation, interviews, and documentation is given. The results of this study indicate that the concept of entrepreneurship education developed in Tarbiyah faculty colleges in Aceh is by providing entrepreneurship education materials and practices so that students have the spirit and additional skills needed after students graduate so that they are able to become entrepreneurs independently. The implementation of entrepreneurship education in lectures to foster an entrepreneurial spirit for Tarbiyah faculty students is carried out through a learning process of direction and example. Entrepreneurship learning is carried out by providing practical material so that students can have more experience and have a good entrepreneurial mentality. Practices include thinking about what to sell, making business products directly, selling and marketing products online or offline. The obstacle is the lack of funds and facilities available to support student practical activities.